3.0k views
7 votes
If f(x)--2 and g(x)=2x²+x-3, find (f+g)(x).

User Scottie
by
5.5k points

1 Answer

10 votes

Answer and Step-by-step explanation:

We are given two functions and are asked to solve a composite function.

f(x) = 2

g(x) = 2
x^2 + x - 3

All we have to do are add the functions together.

(2) + (2
x^2 + x - 3) = 2
x^2 + x - 1

I hope this helps!
#teamtrees #PAW (Plant And Water)

User Marouane Gazanayi
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.